Knowledge and practices of health workers on safe disposal of sharp medical wastes in selected hospitals (Asian Journal of Medical and Biological Research, 2021)
Sharp medical waste is infectious and hazardous because of their high potential diseases transmission and injury. It poses serious threats to environmental health. A cross sectional study was done to assess the level of knowledge and practices of health workers on safe disposal of sharp medical wastes. This study was done in Pirojpur Sadar Hospital, Nazirpur Upazilla Health Complex and Zia Nagar Upazilla Health Complex. Sample size was 200 Health Workers. A Semi-structured interviewer administered questionnaire was used for data collection. The collected data were processed and analyzed with the help of SPSS (Version 20) software on the basis of different variables. The period of study was from January to December 2016. The study result shows that among 200 respondent mean age was 44.05 (±7.01) years. The designation varieties were nurses (70.0%), doctor (10.0%), Aya/ward boy (15.0%). This study found that, majority of the respondents had knowledge about the concept of medical waste and sharp medical waste. Among the respondents (90.0%) respondents knew the correct color bin to segregate sharp medical waste. Multiple responses of the respondents (80%) mentioned that they got information from Course curriculum. Knowledge of the respondents on sharp medical waste disposal (64.5%) had Good knowledge, (23%) had Fair Knowledge and (12.5%) had Poor Knowledge. Most of the respondents (47.5%) had Good practices, (33%) had Fair and (20%) had Poor practices regarding safe disposal of sharp medical waste disposal. Adequate supply of equipment’s and strict monitoring system should be established to improvement the practice of the health care providers regarding safe disposal of sharp medical waste. Training on sharp medical waste disposal will help the participants to improve their knowledge and practices.Asian J. Med. Biol. Res. December 2020, 6(4): 802-808